Closing Address - H. Wagner (The Southern African Institute of Mining and Metallurgy, 1988)
It is a great privilege for me to have been asked to present the closing address to this most successful symposium on backfill in the South African mining industry. When I accepted this invitation I did not fully appreciate the tremendous progress made on most aspects of backfilling in the last few years. The number and quality of papers presented at this symposium bear testimony to the mining industry's determination and success in introducing backfill in underground mines to improve strata control and environmental conditions, and to provide better protection to mineworkers against the hazards of rockbursts and rockfalls. Many contributions demonstrated that these benefits can be achieved at a reasonable cost, and in some instances improved grade and higher rate of face advance result in improved economics. In my closing address I will attempt to summarize the progress made in the various aspects of backfilling underground workings and to identify those areas which, in my opinion, require further attention and effort. I will undertake this review under the following main headings: ? fundamentals of backfilling; ? design of backfill systems; ? operation of backfill systems; ? control of backfill systems; and other aspects of backfill systems.